Energy loss for droplets bouncing off superhydrophobic surfaces - Thenarianto, Calvin (2023)
A water droplet can bounce off superhydrophobic surfaces multiple times before coming to a stop. The energy loss for such droplet rebounds can be quantified by the ratio of the rebound speed UR and the initial impact speed UI; i.e., its restitution coefficient e = UR/UI. Despite much work in this area, a mechanistic explanation for the energy loss for rebounding droplets is still lacking. Here, we measured e for submillimeter- and millimeter-sized droplets impacting two different superhydrophobic surfaces over a wide range of UI (4-700 cm s-1). We proposed simple scaling laws to explain the observed nonmonotonic dependence of e on UI. In the limit of low UI, energy loss is dominated by contact-line pinning and e is sensitive to the surface wetting properties, in particular to contact angle hysteresis Δ cos θ of the surface. In contrast, e is dominated by inertial-capillary effects and does not depend on Δ cos θ in the limit of high UI.